School Counselors' Efforts in Implementing Career Guidance Services - Mushbihah Rodliyatun; Sutrisno Sutrisno; Abnadee Salaeh; Muhammad Nazil Iqdami (Program Studi BKPI IAIN Salatiga, 2022)
This study aims to determine the roles and responsibilities of school counselors regarding student career services, as well as the form of school counselors' efforts in implementing career guidance services in SMK Al Falah Salatiga. This qualitative phenomenological study involved a school counselor and 39 11th-grade students. Primary and secondary data were collected through observation, interview, and documentation, and analyzed using data reduction, presentation, and conclusions. The study's finding demonstrates that (1) The school counselor's role in career advice services is to identify issues and address them, as well as to identify potentials as informants and career educators, facilitators, determinants, and implementers of career counseling programs. (2) The types of career advice services included: (a) orientation services; and (b) information technology services, which were delivered through websites and WhatsApp groups, power point files, pdf, eBooks, and learning videos; (c) Placement and distribution services, which were done through internship programs to direct students' skills.